Invasion of Pheochromocytoma from the Caudal Vena Cava to the Right Ventricular Cavity in a Dog. (11th February 2020) - Machida, Takafumi; Machida, Noboru
Abstract : Pheochromocytomas are catecholamine-secreting tumors that are composed of neuroectoderm-derived chromaffin cells. An 8-year-old miniature dachshund with abdominal distension was diagnosed with a neuroendocrine tumor with invasion from the caudal vena cava to the right ventricular cavity. The dog died due to hypotensive shock from the vagal reflex, and on autopsy, an extra-adrenal pheochromocytoma (paraganglioma) was diagnosed in the caudal abdomen. At autopsy, the tumor plug of the caudal vena cava was confirmed. To the best of our knowledge, this is the first case report that echo-captured the extension of pheochromocytoma in the right ventricle and shows it in a figure and video file.